Studi Perbandingan Keoptimalan Hasil Desain Struktur Rangka Gewel Baja Dengan Beban Angin Menurut PPIUG 1983 Dan SNI 1727:2013 - Lapudooh, Tommy; Hunggurami, Elia; Pah, Jusuf J. S. (P3M- Politeknik Negeri Kupang, 2024)
In Indonesia there are several basic literature on wind load planning, such as PPIUG 1983 and SNI 1727:2013. The transition from PPIUG 1983 to SNI has a different concept of wind load. In this study, the optimization of gewel structure design will be compared using both standards. The purpose of this study was to determine the difference in wind load calculation and also to determine the optimization of gewel structure design due to wind load PPIUG 1983 and SNI 1727:2013. Based on the results of research on SNI 2013 the value of wind pressure is not determined based on the distance from the building site to the waterfront but must take into account wind speed, wind direction coefficient, exposure category, topographic factors, wind blowing coefficient, internal pressure coefficient, velocity pressure exposure coefficient, external pressure coefficient and after that just calculate the value of wind pressure on a structure. In PPIUG 1983 the value of wind pressure on the structure is determined by the distance from the location of the building to the waterfront, except for certain areas that may produce a blow pressure greater than there is already determined then P is calculated using the formula V2/16. For the optimization of the calculation results that have been done, it is known that the design of wind loads for a building height of 7 meters based on wind loads in accordance with SNI 2013 is more optimal because there are still some structural elements that meet the saturation ratio standards set. Di Indonesia terdapat beberapa literatur dasar perencanan beban angin, seperti PPIUG 1983 dan SNI 1727:2013. Peralihan dari PPIUG 1983 ke SNI memiliki konsep beban angin yang berbeda. Dalam penelitian ini, akan dibandingkan keoptimalan desain struktur gewel menggunakan kedua standar tersebut. Tujuan penelitian ini adalah untuk mengetahui perbedaan perhitungan beban angin dan juga mengetahui keoptimalan desain struktur gewel akibat beban angin PPIUG 1983 dan SNI 1727:2013. Berdasarkan hasil penelitian pada SNI 2013 nilai tekanan angin tidak ditentukan berdasarkan jarak dari lokasi bangunan ke tepi pantai namum harus memperhitungkan kecepatan angin, koefisien arah angin, kategori eksposur, faktor topografi, koefisien tiupan angin, koefisien tekanan internal, koefisien eksposur tekanan velositas, koefisien tekanan eksternal dan setelah itu baru menghitug nilai tekanan angin pada suatu struktur. Pada PPIUG 1983 nilai tekanan angin pada struktur ditentukan dengan jarak dari lokasi bangunan ke tepi pantai, kecuali daerah-daerah tertentu yang mungkin menghasilkan tekanan tiup yang lebih besar dari ada yang sudah ditentukan maka P dihitung dengan menggunakan rumus V2/16. Untuk keoptimalan dari hasil perhitungan yang telah dilakukan diketahui bahwa desain beban angin untuk ketinggian bangunan 7 meter berdasarkan beban angin sesuai dengan SNI 2013 lebih optimal dikarenakan masih ada beberapa elemen struktur yang memenuhi standar rasio keterpenuhan yang ditetapkan